From Institutional Sustainability to Human Behavioral Engagement: An Adaptive Governance Perspective in the Mining Sector – A Literature Review - Majid Ansari; Inti Englishtina; Honorata Ratnawati Dwi Putranti (Proceeding of The International Conference on Business and Economics, 2026)
The mining sector is widely recognized as a high-risk industry characterized by complex social, environmental, and organizational challenges. In response, sustainability governance in mining has predominantly relied on institutional mechanisms such as regulations, voluntary standards, and sustainability reporting frameworks. However, growing evidence indicates that these approaches often fail to generate substantive sustainability outcomes because they insufficiently address human and organizational dimensions. This literature review aims to synthesize existing research on sustainability governance in the mining sector by shifting the analytical focus from institutional sustainability to human behavioral engagement. Using a systematic and thematic literature review approach, this study analyzes peer-reviewed articles indexed in Scopus that examine sustainability governance, human behavior, and organizational dynamics in the mining sector. The findings reveal a persistent gap between formal sustainability commitments and actual practices, frequently manifested in symbolic compliance and greenwashing. The review further demonstrates that human behavior—shaped by employee engagement, trust, perceived justice, and organizational culture—plays a decisive role in determining the effectiveness of sustainability governance. Moreover, the literature highlights the limitations of rigid, top-down governance models in managing the complexity and uncertainty inherent in mining systems, emphasizing the relevance of adaptive governance approaches that promote learning, flexibility, and stakeholder participation. This study contributes to the literature by integrating institutional, behavioral, and adaptive governance perspectives into a human-centered framework. Practically, it underscores the strategic role of human resource management in translating sustainability commitments into meaningful behavioral change and long-term sustainability outcomes in the mining sector.